Water plazas as innovative approaches for managing urban stormwater - Johansson, Julia (2019)
Urbanisation in combination with a changing climate put high pressure on future cities to deliver sustainable, liveable and attractive urban places. Traditionally, many green and blue spaces in cities have been removed and replaced with impervious pavements or buildings in order to manage the need for densification. This have resulted in an affected hydrological cycle that no longer operate in urban areas the same way as it does in natural conditions. When precipitation is increasing and extreme rainfalls occurs more frequently, the hardscaped cities cannot manage the amount of water and urban flooding is a fact. This leads to an urging need for climate adaptation and modernisation of the conventional way to manage stormwater. One way of managing stormwater in a more sustainable way is the concept of Water plazas. Basically, it is a plaza that will be dry and available for people to enjoy most time of the year but which after a heavy cloudburst temporarily can store rainwater. In this way flooding of surrounded buildings and infrastructure may be prevented.